A Simplfied Voltage Vector Selection Strategy for Direct Torque Control - Li Yaohua Li Yaohua; Liu Jingyu; Ma Jian Ma Jian; Yu Qiang Yu Qiang (Universitas Ahmad Dahlan, 2011)
The direct torque control (DTC) for permanent magnet synchronous motor (PMSM) under the control of switching table suffers from high torque ripple and variable switching frequency. For PMSM DTC system, voltage vector selection strategy as the hysteresis control principle determines the system’s performance. The angle (a) between stator flux vector and the applying voltage vector determines effect of the voltage vector on the amplitude of stator flux and torque angle. The effect of the voltage vector on toque is dependent on a, torque angle and parameters of PMSM. A voltage vector selection strategy based on the technology of space vector modulation (SVM) is proposed to control stator flux, torque angle and torque. Experimental results for a 15-kW interior PMSM show it can decrease stator current and torque ripples and fix the switching frequency.